Períodos de interferência de plantas daninhas nas culturas da chia e quinoa - Pinheiro , Jordanya Ferreira (2022)
The objective of the study was to evaluate the effect of weed competition on the development of chia and quinoa plants and to determine the periods of interference. For chia, the experiment was conducted in a randomized block design, in 2x2x20 factorial scheme, with four repetitions, with two sowing densities (20 and 40 plants m-1), two types of management: control and coexistence and 20 periods, 10 (clean) and 10 (weeds) with 0, 7, 14, 21, 28, 35, 42, 49, 56, and 98 days after emergence (DAE). For the quinoa crop, the experimental design was randomized blocks in 2x8 factorial scheme, with two types of management: coexistence and control of the weed community with the crop and eight weeding seasons corresponding to the periods of coexistence and control of weeds in the crop, with four repetitions. The periods of coexistence and control were: 0, 9, 18, 27, 36, 45, 54 and 70 days after emergence (DAE). The determination of the period before interference (PAI), total interference prevention period (PTPI) and interference prevention control period (PCPI) was carried out based on the adjustment to regression models. Weed competition interfered with the development of chia plants regardless of sowing densities, because weed competition reduced the relative growth rate (RCR) by 12.50% in relation to the control. The critical period for prevention of interference (PCPI) of weeds in chia at sowing density of 20 plants m-1 was between 14 and 57 DAE, while for sowing density of 40 plants m-1 was between 12 and 50 DAE. In other words, the increase in plant density in the seeding line promoted greater interspecific competition of the chia crop with the weed community, providing a reduction of 5 days of the PCPI. In the quinoa crop, weed competition reduced the productivity of the crop by 28.9% and, considering a 5% loss in productivity, the PAI of 4 DAE, the PTPI of 70 DAE, and PCPI of 4 to 70 DAE were defined. Therefore, it is necessary to control weeds from the first days after crop emergence until the end of the cycle. Determining this period will allow decisions to be made in crop management to minimize losses produced by weed interference. In general, for chia, the use of the lower sowing density increased the crop productivity, as well as the PCPI in relation to the cultivation at the highest sowing density, by up to 5 days. On the other hand, for quinoa, weed control is necessary from the first days after crop emergence until the end of the cycle.